2020
DOI: 10.1111/pce.13831
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase Dα1 mediates the high‐Mg2+ stress response partially through regulation of K+ homeostasis

Abstract: Intracellular levels of Mg2+ are tightly regulated, as Mg2+ deficiency or excess affects normal plant growth and development. In Arabidopsis, we determined that phospholipase Dα1 (PLDα1) is involved in the stress response to high‐magnesium conditions. The T‐DNA insertion mutant pldα1 is hypersensitive to increased concentrations of magnesium, exhibiting reduced primary root length and fresh weight. PLDα1 activity increases rapidly after high‐Mg2+ treatment, and this increase was found to be dose dependent. Two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 92 publications
(123 reference statements)
1
15
0
Order By: Relevance
“…Knockout line pldα1-1 (SALK_067533) was obtained from the NASC. Complemented lines pldα1-1 Com1 and pldα1-1 Com2 were described previously ( Kocourková et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Knockout line pldα1-1 (SALK_067533) was obtained from the NASC. Complemented lines pldα1-1 Com1 and pldα1-1 Com2 were described previously ( Kocourková et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…Plates were kept in a growth chamber at 22°C during the day, 21°C at night, under long day (16h of light) conditions at 100μmolm −2 s −1 of light. Hydroponic plant cultivation was described in Kocourková et al (2020) . Twenty-four-day-old hydroponically cultivated plants were treated with either ½ Hoagland’s solution (control) or ½ Hoagland’s solution with 15mM MgSO 4 added.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The accumulation of Ca 2+ and Mg 2+ has been reported to be associated with LK response (Behera et al 2016;Kocourková et al 2020;Dong et al 2021), and we measured the content of Ca 2+ and Mg 2+ in both JZ18 and JZ34 plants after LK treatment. The content of Ca 2+ and Mg 2+ were higher in the root of JZ34 than JZ18,while there were no significant difference in the shoots (Fig.…”
Section: Na + K + Ca 2+ and Mg 2+ Content In Roots And Leaves Of Jz18 And Jz34 Plantsmentioning
confidence: 99%
“…By contrast, in root and shoot tissues, the JZ34 showed lower Na + content than the JZ18 plants, which caused a higher Na + /K + ratio in JZ18 plants after LK stress. Especially, after LK treatment for 7 days in the roots, these Na + /K + ratio existed a significant difference between JZ34 and JZ18 plants, showing that the damage of ion homeostasis becomes more serious as the treatment time of LK stress increases in the roots of JZ18 plants.Recent research found that high concentrations of Mg 2+ disrupt K + homeostasis, and that transcription of K + homeostasis-related genes CIPK9 and HAK5 is changed to limit the elongation of root length (Kocourková et al 2020)…”
mentioning
confidence: 99%